Preoperative Analgesia Efficacy of Liposomal Bupivacaine Following Pericapsular Nerve Group (PENG) Block in Patients with Hip Fracture: A Randomized Controlled Observer-Blinded Study - Haobin Peng; Jiajun Wen; Manli Chen; Zhengyuan Xia; Ying Jiang; Kaiqi Xie; Weitao Huang; Bangsheng Cui; Peixing Li; Yiwen Zhang; Xianping Wu (Pain and Therapy)
Abstract Introduction Single-injection pericapsular nerve group (PENG) block with ropivacaine provides clear analgesic effects in preoperative pain management for hip fractures. However, it suffers from insufficient duration, failing to meet the needs of most patients. This single-center, randomized controlled, observer-blinded trial utilizes a novel combination of liposomal bupivacaine (LB) single-injection PENG block to examine its efficacy, duration, and safety in preoperative analgesia for hip fractures, aiming to develop a new preoperative analgesic protocol. Methods Sixty-six patients with hip fractures received ultrasound-guided single-injection PENG block with LB or ropivacaine after admission. The primary outcome was the static and dynamic pain scores measured at 48 h post-block. Pain scores at 12, 24, 36, 60, and 72 h post-block, rescue analgesia rate, time to first opioid, additional morphine consumption, and adverse events were assessed as the secondary outcomes. Results LB versus ropivacaine group at 48 h post-block, with a median interquartile range (IQR) of 2 (1.0–2.0) versus 3 (2.0–3.0) at static pain score and 2 (1.75–3.0) versus 4 (4.0–5.0) at dynamic pain score. LB group had lower dynamic and static pain scores at other observation points except for the static pain score at 72 h, lower pain intensity [sum of pain intensity difference (SPID)0–24, SPID0–48 and SPID0–72], longer time to first opioid, lower additional morphine consumption, and lower incidence of nausea and vomiting. No significant inter-group differences were detected in other secondary outcomes. Conclusions For preoperative analgesia of hip fractures, LB single-injection PENG block had a similar analgesic intensity and safety as ropivacaine but provided a longer duration of analgesia, reaching 48 h and even extending beyond 60 h, which reduced opioid consumption and extended time to the first opioid. Trial Registration The protocol was registered in  www.chictr.org.cn  under the identifier ChiCTR2300072939.